Provincial Economic Convergence in Post-Decentralization Indonesia: A Panel Analysis from 2000 to 2022 - Aulia, Hanna Hilyati; Puspita Sari, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This study examines the dynamics of economic convergence across Indonesian provinces during the period 2000–2022 by employing β-convergence, σ-convergence, and the Williamson Index. Provincial GDP per capita at constant 2010 prices is analyzed within a panel data framework. The results indicate significant β-convergence, implying that provinces with lower per capita income have grown faster than wealthier provinces. The σ-convergence analysis reveals a long-term decline in income dispersion across provinces, although temporary fluctuations occurred during the global financial crisis and the COVID-19 pandemic. The Williamson Index also exhibits a downward trend, indicating a more equal distribution of income among provinces. These findings suggest that fiscal decentralization and infrastructure development have contributed to reducing regional inequality, although the convergence process has been relatively moderate